2018
DOI: 10.1002/casp.2349
|View full text |Cite
|
Sign up to set email alerts
|

“How can you make friends if you don't know who you are?” A qualitative examination of international students' experience informed by the Social Identity Model of Identity Change

Abstract: This paper explores the contribution of social identity change to international students' health and well‐being. International students typically face a range of challenges from the time they leave their home country, including the need to adapt both to a new culture and norms and to a new educational landscape. Previous research informed by the Social Identity Model of Identity Change (SIMIC) suggests that during such life transitions, an individual's group memberships and associated social identities can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
4
50
0
3
Order By: Relevance
“…An absence of social support (Zhang & Goodson, ) and differences in values between their cultures of origin and U.S. culture (Lee & Carrasquillo, ) may negatively affect international students struggling to adapt to the cultural norms of the academic environment. For example, Ng, Haslam, Haslam, and Cruwys () explored international students’ social identity change in adjusting to the United States and found that cultural differences were a significant barrier to the students forming meaningful friendships and social connections. One international student participant explained, “For my new friends here, because we don't know each other deep, you do not know how they think, how is the way they ask each other.…”
Section: International Students’ Challenges In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…An absence of social support (Zhang & Goodson, ) and differences in values between their cultures of origin and U.S. culture (Lee & Carrasquillo, ) may negatively affect international students struggling to adapt to the cultural norms of the academic environment. For example, Ng, Haslam, Haslam, and Cruwys () explored international students’ social identity change in adjusting to the United States and found that cultural differences were a significant barrier to the students forming meaningful friendships and social connections. One international student participant explained, “For my new friends here, because we don't know each other deep, you do not know how they think, how is the way they ask each other.…”
Section: International Students’ Challenges In the United Statesmentioning
confidence: 99%
“…One international student participant explained, “For my new friends here, because we don't know each other deep, you do not know how they think, how is the way they ask each other. Just, for me, I just always scared that I'll say something wrong” (Ng et al, , p. 178). Although international students may have acquaintances, meaningful social connections are far less common.…”
Section: International Students’ Challenges In the United Statesmentioning
confidence: 99%
“…The user experience was measured quantitatively and desirability. We also assessed the predictive validity of the oSIM, hypothesizing that it should be able to replicate associations with well-being previously demonstrated in the social cure literature (e.g., as reviewed by Ng et al, 2018). Finally, contextual adaptability was assessed by examining the relationship between oSIM variables and contextually-specific outcome measures that are theoretically and/or practically relevant in a particular domain (e.g.,…”
Section: Research Aimsmentioning
confidence: 99%
“…Increasingly, researchers are interrogating the psychological mechanisms that underpin the associations between social connection and personal wellbeing (Fritsche, Jonas, & Fankhänel, 2008;Greenaway, Wright, et al, 2015). In particular, programmatic work informed by a social identity approach points to the value of studying the mechanisms that underpin what have been referred to as 'social cure' effects (Jetten, Haslam, & Haslam, 2012;Ng, Haslam, Haslam, & Cruwys, 2018). Nevertheless, it remains the case that researchers' capacity to assess social identity is limited by the measurement tools at their disposal.…”
Section: Social Identity Mapping Onlinementioning
confidence: 99%
See 1 more Smart Citation